Gentamicin in neonates with hemodynamically significant patent ductus arteriosus - Kannan Sridharan; Abdulraoof Al Madhoob; Muna Al Jufairi; Eman Al Ansari; Reem Al Marzooq; Zakariya Hubail; Sadiq Jaafar Hasan (Wolters Kluwer Medknow Publications, 2023)
Background: Gentamicin has been shown to cause vasodilation in preclinical studies. Hemodynamically significant patent ductus arteriosus (hsPDA) is a commonly observed congenital heart disorder in preterm neonates. Concomitant gentamicin theoretically shall delay the closure/result in nonclosure of ductus arteriosus (DA). Similarly, hsPDA can alter the pharmacokinetics of gentamicin and so trough gentamicin concentrations. We carried out the present study to evaluate the association between gentamicin use and closure of hsPDA (treated with acetaminophen) as well as the effect of hsPDA on trough concentrations. Methods: This study was a prospective, observational study that included 60 neonates diagnosed with hsPDA by echocardiography and 102 neonates without hsPDA. Demographic details, size of DA as per echocardiography at the end of treatment with acetaminophen, gentamicin-dosing regimen, and trough concentrations were collected. Standard definitions were adhered in classifying the gestational age, birth weights, and size of DA. The numerical values are reported in median (range). Results: Neonates with hsPDA had significantly lower daily doses of gentamicin [4.5 (2.5-10), 7 (3.2-13) mg; P < 0.001] but longer duration of therapy [8 (3-14), 5 (3-7) days; P < 0.001] than those without hsPDA in very preterm neonates. No significant differences were observed in the trough concentrations of gentamicin between the groups. No association was observed between gentamicin use and closure of DA. However, those with successful closure of DA received gentamicin for a longer duration [6 (3-10), 4 (3-14) days; P < 0.05] that was independent of acetaminophen duration and had received higher cumulative doses of gentamicin. Conclusion: In conclusion, we observed a significantly longer duration of gentamicin therapy in neonates with hsPDA compared to those without hsPDA. No significant differences were observed in the rates of closure of DA with concomitant gentamicin administration and gentamicin trough concentrations.